2016
DOI: 10.1371/journal.pone.0168426
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo, Non-Invasive Characterization of Human Bone by Hybrid Broadband (600-1200 nm) Diffuse Optical and Correlation Spectroscopies

Abstract: Non-invasive in vivo diffuse optical characterization of human bone opens a new possibility of diagnosing bone related pathologies. We present an in vivo characterization performed on seventeen healthy subjects at six different superficial bone locations: radius distal, radius proximal, ulna distal, ulna proximal, trochanter and calcaneus. A tailored diffuse optical protocol for high penetration depth combined with the rather superficial nature of considered tissues ensured the effective probing of the bone ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…This study extends previous work that demonstrated the potential of NIRS measurements of blood in tibial cortical bone using cuff inflation in a single subject 22 and in different superficial bones using a single-layer system 25 . In this work we demonstrate that NIRS is able to measure significant physiological changes in blood perfusion during exercise in a cohort of able-bodied individuals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study extends previous work that demonstrated the potential of NIRS measurements of blood in tibial cortical bone using cuff inflation in a single subject 22 and in different superficial bones using a single-layer system 25 . In this work we demonstrate that NIRS is able to measure significant physiological changes in blood perfusion during exercise in a cohort of able-bodied individuals.…”
Section: Discussionsupporting
confidence: 87%
“…Aziz et al 22 presented hemoglobin content in tibia cortical bone in a single individual during cuff inflation using a NIRS instruments developed specifically for bone. Sekar et al 25 used time-resolved diffuse optical spectroscopy to probe bone oxygen consumption and blood flow in different superficial bones in able-bodied individuals. These promising results indicate the potential of optical techniques in investigating blood content in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic wavelength selection of the supercontinuum source (SC450, Fianium, UK) was achieved by dispersing the light using a rotating prism and selecting a narrow band with a slit. The system was mounted on a cart and permitted non-invasive clinical studies on the application of broadband diffuse optics to bone tissues [29] and thyroid [68]. The introduction of compact commercial supercontinuum sources based on fiber amplified lasers coupled to photonic crystal fibers [62][63][64] and of rugged silicon photomultipliers [65] usable in diffuse optics [43,66] made it possible to realize movable rack-based systems suitable for use in clinical settings, as shown in Figure 6 [23,67].…”
Section: Instrumentation/technology For Broadband Td-dosmentioning
confidence: 99%
“…In vivo applications of diffuse optics are mostly explored in the therapeutic window (600-1100 nm), where light attenuation in human tissues is comparatively low [25][26][27][28]. Furthermore, quantification of tissue constituents (chromophores) can be performed through the Beer-Lambert law, by a linear fit of typical tissue constituent absorption spectra with the broadband absorption spectrum of in vivo tissue [29,30]. Information on the microscopic structure, useful for tissue characterization, can also be derived from the scattering properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation